Intraindividual comparison between femtosecond laser–assisted and conventional cataract surgery. Issue 2 (February 2017) - Mursch‐Edlmayr, Anna S.; Bolz, Matthias; Luft, Nikolaus; Ring, Michael; Kreutzer, Thomas; Ortner, Christoph; Rohleder, Matthias; Priglinger, Siegfried G.
Abstract : Purpose : To compare the safety and efficacy between femtosecond laser–assisted cataract surgery using the Victus laser system and conventional cataract surgery. Setting : Department of Ophthalmology, Kepler University Hospital, Linz, Austria. Design : Prospective randomized case series. Methods : Both eyes of patients with age‐related cataract were randomized to conventional cataract surgery or femtosecond laser–assisted cataract surgery, both with intraocular lens (IOL) implantation. Postoperative follow‐up was at 1 day, 1 week, 1 month, 3 months, and 6 months and comprised corrected distance visual acuity, endothelial cell density (ECD), central corneal thickness (CCT), and central retinal thickness. The main outcomes were intraoperative and postoperative complications and the effective phacoemulsification time (EPT). Intraocular lens and capsulotomy centration were evaluated using retroillumination slitlamp photography. Results : The study enrolled 50 patients. No intraoperative complications occurred in either group. The ECD, CCT, and central retinal thickness were similar between the groups at all follow‐up examinations ( P > .05). The EPT was not statistically significantly different between the groups ( P = .22). The IOL centration was similar between the groups ( P = .93). Conclusion : Femtosecond laser–assisted and conventional cataract surgery using the mentioned system were equally safe and effective.